Discriminative Psychological Skills For Basketball Players And Its Relation With Sport Defensive Featires - Hassan, Seham (Journal of Physical Education, 2009)
A The study aims to specify the sport defensive features that discriminates Basketball players, and psychological skills that participates in developing it and recognizing the relation species between psychological and defensive skills that discriminates Basketball players in this study. The estimation sport defensive measurement was applied, which is designed by "Ttko" and "Richard", modulated and quoted by Dr. Mohamed Hassan Alawy and inquiring psychological skills measurement was designed by "Stephan Bill" , "John Alinson" and "Christopher Shambrok" Dr. Mohamed Hassan Alawy had prepared and translated it in to Arabic Language. It was applied on Basketball players in Alexandria Clubs (Smouha - Sporting) , and the study had reached to determine the sport defensive Features that discriminates Basketball players, the results that there is a positive relation between some sport defensive features and psychological skills which discriminates Basketball players